A systematic review of complications related to laparoscopic and laparoscopic‐assisted procedures in dogs. (25th April 2020) - Maurin, Marie‐Pauline; Mullins, Ronan A.; Singh, Ameet; Mayhew, Philipp D.
Abstract: Objective: To evaluate and report the quality of the scientific literature reporting complications associated with laparoscopic and laparoscopic‐assisted procedures in client‐owned or healthy research dogs and to report and illustrate laparoscopic complications related to individual organ systems. Study design: Systematic review. Animals: Client‐owned or healthy research dogs. Methods: A literature review was performed by using PubMed and CAB abstracts for English‐language studies providing descriptions of complications related to laparoscopic and laparoscopic‐assisted procedures in dogs. Study selection used PRISMA (Preferred Reporting Items for Systematic reviews and Meta‐Analyses) guidelines. Quality assessment was performed by using a MINORS (Methodological Items for Non‐Randomized Studies) scoring system and a grading scale of level of evidence. Descriptive statistics were used. Results: In total, 741 manuscripts were identified, with 64 manuscripts eligible for data extraction and quality assessment. The most represented organ system was the female genital tract, represented by 22 (34.4%) studies. The most commonly reported intraoperative and postoperative complications were related to abdominal entry and portal incisions, respectively. In 53 of 54 non‐randomized studies, high risk of bias was found. Forty‐eight (75%) studies provided level III or IV evidence. Conclusion: This report provides an updated review of complications related to laparoscopic and laparoscopic‐assisted procedures in dogs, classified by organ system. The overall quality of evidence was low, limiting direct comparison of complication rates between studies. Clinical significance: There is a need for implementation of standardized criteria for defining complications, study time frames and greater numbers of high quality prospective randomized trials in veterinary laparoscopy to permit comparison of complication and conversion rates between published studies and across organ systems.